Application of Soundproofing Materials for Noise Reduction in Dental CAD/CAM Milling Machines - Eun-Sung Song; Young-Jun Lim; Joongsoo Lee; Jung-Bon Moon; Bongju Kim (Applied Sciences, 2020)
Soundproofing materials are widely used in various fields as a passive measure to reduce noise. Despite this, there have been a few studies on the application of soundproofing materials on medical equipment, which is the main cause of noise in a medical environment. Despite the increasing number of studies on active noise control for the noise reduction of machines, it is difficult to apply customized noise control—i.e., specific control measures according to the various characteristics of that noise—due to its high cost and low effectiveness. Therefore, research on passive noise control using soundproofing materials is required for effective noise control. The 3D CAD/CAM milling machine, which is an essential device in the digitalized dental environment, is causing various problems as a new noise source. This study investigated the noise of the milling machine and considered its characteristics in application of an efficient soundproofing material for noise reduction. Additionally, a soundproofing material performance test was conducted to select an appropriate soundproofing material based on the noise characteristics of the milling machine. As milling machines cause noise issues in hospitals, the study results were analyzed in considering practical aspects for immediate application to actual sale products. This study suggests that the application of Thinsulator and a triple soundproofing mat (butyl 100% + aluminum + sound-insulating material) is effective in the noise reduction of milling machines.